2015
DOI: 10.1109/tpds.2014.2316834
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Computation Offloading Game for Mobile Cloud Computing

Abstract: Mobile cloud computing is envisioned as a promising approach to augment computation capabilities of mobile devices for emerging resource-hungry mobile applications. In this paper, we propose a game theoretic approach for achieving efficient computation offloading for mobile cloud computing. We formulate the decentralized computation offloading decision making problem among mobile device users as a decentralized computation offloading game. We analyze the structural property of the game and show that the game a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
427
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(444 citation statements)
references
References 27 publications
3
427
0
1
Order By: Relevance
“…Most existing studies focused on o oading of mobile users' tasks to remote clouds by exploring di erent pricing models or di erent e cient energy-conserve task scheduling approaches, such as [10 16]. For example, the author of [14] formulates the decentralized computation o oad decision making problem among mobile device users as a decentralized computation o oading game, analyzed the structural property of the game and showed that the game always admits a Nash equilibrium. The authors of [15] investigates the problem of how to conserve energy for the resource-constrained mobile device, by optimally executing mobile applications in either the local mobile device or the cloud.…”
Section: Related Workmentioning
confidence: 99%
“…Most existing studies focused on o oading of mobile users' tasks to remote clouds by exploring di erent pricing models or di erent e cient energy-conserve task scheduling approaches, such as [10 16]. For example, the author of [14] formulates the decentralized computation o oad decision making problem among mobile device users as a decentralized computation o oading game, analyzed the structural property of the game and showed that the game always admits a Nash equilibrium. The authors of [15] investigates the problem of how to conserve energy for the resource-constrained mobile device, by optimally executing mobile applications in either the local mobile device or the cloud.…”
Section: Related Workmentioning
confidence: 99%
“…Consider maximum data computation is 100 GB and maximum offered bandwidth is Hz [11]. For this scenario, we have chosen not to offload until 10% of maximum data is to be computed or 10% of maximum BW is offered.…”
Section: Probability Of Offloadingmentioning
confidence: 99%
“…Most of these research devised a variety of approaches to implement energy saving, time saving and both energy and time saving strategies in computation offloading for mobile cloud computing [28], [10], [22], [7]. Some of these researches have proposed sending computationally intensive tasks to nearby mobile devices with higher computational resources [28], [10].…”
Section: Related Workmentioning
confidence: 99%
“…Others have identified elastic computation offloading methods in which resource intensive applications are partitioned into user interaction activities and computational activities and some parts of the computational activities are sent to surrogates or remote servers for efficient and timely processing whiles the mobile devices process the other parts locally [7], [18], [24]. Some other works have also proposed the complete cloning, mirroring or imaging of a mobile device system together with its operating system and applications and sending the mirrored or cloned image to a clone cloud server located at a remote place for processing and the results sent back to the mobile devices [10].…”
Section: Related Workmentioning
confidence: 99%